Peranan E-Service Quality dan E-Marketing Mix sebagai Penentu Kepuasan dan Loyalitas Pelanggan di Industri E-Commerce Indonesia - Pratama, Yohanes Dwi; Dahlan, Kandi Sofia (Journal of Business & Applied Management, 2023)
The role of E-S-Qual scale on e-service quality variables can be used to measure the quality of services provided by Tokopedia toward customer and the e-marketing mix variabel can be used by organizational management so that they can win the competition in digital sales through e-commerce. Therefore, this research was conducted to analyze the role of e-service quality and e-marketing mix that can create customer satisfied and loyal. The sample was selected based on non-probability sampling technique and 373 people were selected as respondents. Data from filling out the questionnaire was processed using the structural model equation method with AMOS 26 software.The results of the study stated that the direct effect of e-service quality was positive and significant on e-satisfaction and e-loyalty. The direct influence of the e-marketing mix variable which is positive and significant is only obtained on its relationship with the e-satisfaction variable. The results of the indirect effect analysis are only proven on the relationship between e-service quality and e-loyalty through the e-satisfaction variable